Les services de soins hospitaliers publics dans l’agglomération de Sfax : spécificités fonctionnelles et pouvoir spatial - Mounir Jarraya; Gérard Beltrando (EchoGéo)
Installed in the town of Sfax, the university hospital structures exert a pull on the device space. This is in the flow of patients attending the agglomeration for various specialty care services offered by these structures. Through the levels of care consultation and hospitalization, we analyze the aspects of the EPS’s space power of the agglomeration of Sfax, focusing on the congestion affecting them as well as the effect of measures adopted until now in order to lighten. Data within the hospital activity shown by indicators (DMS, TRL …) are used in this work resulted in the trend analysis of congestion as well as some propositions to decongest the EPS of Sfax.